Analysis of birth weights of a rural hospital - Ashtekar Shyam (Indian Journal of Community Medicine, 2010)
Background: Low birth weight remains a major reason behind childhood malnutrition. The NFHS findings show no dent in this problem. Objective: This study was undertaken to explore change in birth weights in a period from 1989 to 2007 and any associations thereof. Materials and Methods: All birth records of a private rural hospital spanning two decades (1989-2007) were analyzed for birth weight, age of mother, gender, birth order of the baby, proportion of pre-term babies and low birth weight babies. Results: No change was observed in the average birth weights (average 2.71 kg) over the period. Although the birth weight shows some expected variance with the age of mother, it was found to have no relation with the baby′s birth order and gender. The low birth weight proportion is about 24% and shows little difference before and after the series midpoint of year 1998. Conclusion: The birth weights have hardly changed in this population in the two decades.